Motion control of a 1-DOF pneumatic muscle actuator positioning system - Sakthivelu, Vasanthan; Chong, Shin Horng (2015)
A positioning system driven by a pneumatic muscle actuator was built in order to study the applicability and adaptability of the system into real time applications such as exoskeleton robots and industrial machines. PMA system has many advantages including high power to weight and power to volume ratio, light weight, clean, autonomous and safe. However, the highly nonlinear characteristics of PMA system made it difficult to control. This has been the main challenge in proposing a robust controller for positioning and tracking performance. This study aims to clarify a practical and easy to design controller design procedure for positioning of a PMA system. In addition to positioning performance, the present study focuses on the realization of easy to design a controller without the need for exact model parameters and knowledge in control theory for systems with high nonlinearities. A PI and PID controller using Ziegler-Nicholas design law is proposed and its PTP performance is presented. Finally, the robustness of the proposed controller have been tested in a tracking environment by using triangular and sinusoidal waveform.